Hematological changes in human lymphotropic-T virus type 1 carriers - Ribeiro, Jairo Falcão; Nobre, Akim Felipe Santos; Covre, Louise Canto Ferreira; de Almeida Viana, Maria de Nazaré do Socorro; Silva, Ingrid Christiane; dos Santos, Leonardo Miranda; Ishikawa, Edna Aoba; da Costa, Carlos Araújo; de Sousa, Maísa Silva (Frontiers in Microbiology, 2022)
The Human T-Lymphotropic Virus type 1 (HTLV-1), isolated in 1980, is related to T-cell leukemia/ lymphoma in adulthood, a type of lymphoproliferative disease, and chronic HTLV-1- associated myelopathy, a disease that causes paralysis of the lower limbs, which occur in about 5% of this viral infection. In most cases, HTLV-1 is a slow-progressing virus, considered a virus of low morbidity. This study aimed to establish the hematological profile of patients with HTLV-1 infection in Belém do Pará, describing the hematological parameters under study, estimating the frequency of lymphocytic atypia, and associating the hematological profile with diseases and symptoms. Hematologic data from 202 individuals were analyzed, including 87 HTLV-1 infected individuals and 115 non-HTLV-1 infected individuals as a control group, composed, at a great part, of relatives of the infected. The seroprevalence of HTLV-1 infection was observed in 71.3% of female individuals, with predominance in the group older than 50 years (44.8%). The analysis of hematological parameters showed a significant difference in the counts of the segmented cells (p = 0.0303) and eosinophils (p = 0.0092) in HTLV-1 carriers. Lymphocytic atypia was a finding present only in HTLV-1 carriers (p = 0.0001). There was no high frequency in the leukocyte counts of those infected by HTLV-1 not among them concerning a significant increase or decrease. It is concluded that HTLV-1 infection is prominent in women over 50 years old. The hematological profile of those infected shows a reduction of segmented cells, an increase of eosinophils, and the presence of atypical lymphocytes. The hematological profile of the HTLV-1 carrier should always be evaluated to identify early some diseases associated with the infection.